Entrainment of Juvenile and Adult American Shad at a Pumped Storage Facility. (29th March 2018) - Mathur, Dilip; Heisey, Paul G.; Royer, Doug D.; White, Eric J.; Slowik, Adam C.; Bleistine, Ray A.; Pracheil, Brenda M.; Long, Kimberly A.; Sullivan, Thomas J.
Abstract: The American Shad Alosa sapidissima has been targeted for restoration to the upper Susquehanna River, and entrainment losses at hydroelectric facilities on the river, including the Muddy Run Pumped Storage Facility, are of concern for the potential growth of the American Shad population. Based on the integration of pumping volume, time of entrainment, and literature‐reported diel emigration of juvenile American Shad, the entrainment rate ( N = 145; 53 exposed to pumping) was estimated at 3.5%. The entrainment rate for adults ( N = 507) was estimated at 0.3–3.9%. Using multistate mark–recapture models, the estimated entrainment probabilities (Ψ) of radio‐tagged juveniles were higher during periods of extended pumping (>1 h; Ψ = 0.093; 95% confidence interval [CI] = 0.054–0.156) than at periods of no pumping or short‐duration pumping (<1 h; Ψ < 0.0001; 95% CI = 0.0–0.001); the high extended pumping occurred between 2300 and 0600 hours. Entrainment probabilities for adults were low (Ψ < 0.02); the highest probability occurred for fish detected downstream of the intake during the peak portion of the run (Ψ = 0.015; 95% CI = 0.004–0.047). Entrainment probability for most adult fish did not differ from zero. The low values of Ψ for both life stages were attributed to (1) the deep location of the intake (intake ceiling >11.7 m below the water surface), (2) the surface orientation of American Shad (upper 3.1 m), (3) the low overlap between high‐volume pumping and peak emigration/migration times, (4) the pumping volume relative to prevailing river flows, and (5) the prolonged, robust swimming speed of American Shad, particularly that of adults (>2.2 m/s), which exceeded the intake velocity (0.2–0.9 m/s). Entrainment of juveniles increased with co‐occurrence of low incoming river flows, high pumping volume, and peak emigration times. Quantification of migratory species' entrainment at pumped storage facilities requires integration of diel migration/emigration times with the frequency, timing, and duration of pumping volume.